Analisis Faktor yang Mempengaruhi Kepemimpinan dan Manajemen Sekolah di SMP Negeri Satu Atap 01 Ciseeng (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to comprehensively analyze the factors that influence school leadership and management at SMP Negeri Satu Atap 01 Ciseeng. The background of this study is based on the low effectiveness of school management as indicated by the results of quality evaluations and the limited resources that are characteristic of schools in remote areas. The limitations include aspects of teaching staff, facilities and infrastructure, and low stakeholder involvement in decision-making. The study was conducted from May to June 2025 with a qualitative approach through a case study method. The research subjects included the principal, teachers, school committee, parents of students, and school supervisors. Data collection techniques used in-depth interviews, participatory observation, and documentation studies. Data analysis was carried out using the interactive model from Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions/verification. The results of the study indicate that the effectiveness of school leadership and management is strongly influenced by five main factors, namely: (1) the principal's leadership competence, (2) management of human and material resources, (3) the level of teacher participation in decision-making, (4) a collaborative organizational culture, and (5) strong external support from the school committee and parents. It was found that school principals play a dominant role in developing organizational culture and management strategies, but have not yet optimally engaged teachers and parents. Therefore, it is important to encourage more participatory leadership patterns and openness to cross-role collaboration. This study suggests the need for locally context-based leadership training and the development of policies that support remote school management. By strengthening synergy between stakeholders, it is hoped that school management in remote areas can be more effective and adaptive to the challenges they face.